Simple Model of Soil-structure Interaction in Horizontal Motion Taking into Account the Nonlinearity of the Soil - Shayah, Yaseen; Kollár, László P. (Periodica polytechnica. Civil engineering. Bauingenieurwesen, 2025)
Soil structure interaction is often modeled by lumped parameter models, which consist of connected springs, masses, and dashpots. It was shown that this model – even for the case of elastic behavior – can be rather inaccurate since radiation damping is not properly represented. Pap and her coauthor suggested a simple model that overcomes this problem: a simple infinitely long bar on an elastic foundation connected parallelly to a mass-spring system. Since soil nonlinearity can affect the response considerably, even in the case of moderate seismicity, Pap’s model is extended in this paper for nonlinear soil behavior. As a result, the 3D nonlinear soil can be replaced by a simple beam resting on a foundation and connected parallelly to a mass-spring system. In addition to the three elastic properties, the level of plastification must be prescribed. This model is recommended for the practical modeling of soil-structure interaction when the nonlinearity of the soil is significant.